Cell origin and genome profile difference of penoscrotum invasive extramammary Paget disease compared with its in situ counterpart - Rao, Yamin; Zhu, Jinchao; Zheng, Haiyan; Ren, Yong; Ji, Tianhai (Frontiers in Oncology, 2022)
Penoscrotum extramammary Paget disease (pEMPD) is a rare cutaneous carcinoma with an unknown cell origin. pEMPD always presents as a tumor in situ with an indolent process, whereas some progress into invasive forms with more aggressive behavior. The in situ and invasive cases display different morphologies and biological behavior, and thus far, a relationship between these two components has not been demonstrated. Immunohistochemistry was used to disclose the immunotype of pEMPD, and the results revealed that invasive/in situ pEMPD possessed with some identical immunophenotypes such as CK7, P63, and CK10, which inferred the clonal relatedness. The variable expressions of GCDFP-15 and carcino embryonic antigen hinted that tumor cell origin might be an epidermal sweat gland in epiderma. In our cohort, invasive pEMPD presented increased expression of androgen receptor and decreased MUC5CA expression, and these two changes might bring to the shift of invasive phenotype. To better understanding the relationship between these distinct tumor forms, we performed whole exome sequencing testing to evaluate overlapping genomic alterations of six paired invasive/in situ pEMPDs. The results showed that missense mutation was the predominant mutation type, and C>T transition accounted for 65.1% in all SNP mutation. Among the top 20 differential genes obtained from the six paired invasive/in situ pEMPD analysis, MUC4 (one missense, one in frame del, and one multi-hit), AHNAK2 (two missense and one multi-hit), DOT1L (two missense and one multi-hit), and FRG1 (two missense and one-multi hit) mutations were most enriched in invasive pEMPDs, which postulated that these genes may play roles in the disease progression.